The incidence and prevalence of systemic lupus erythematosus in the UK, 1999–2012. Issue 1 (29th September 2014) - Rees, Frances; Doherty, Michael; Grainge, Matthew; Davenport, Graham; Lanyon, Peter; Zhang, Weiya
Abstract : Objectives: To estimate the incidence and prevalence of systemic lupus erythematosus (SLE) in the UK over the period 1999–2012. Methods: A retrospective cohort study using the Clinical Practice Research Datalink (CPRD). The incidence was calculated per 100 000 person-years and the prevalence was calculated per 100 000 people for the period 1999–2012 and stratified by year, age group, gender, region and ethnicity. Three definitions of SLE were explored: (1) systemic lupus, (2) a fully comprehensive definition of lupus including cutaneous only lupus and (3) requiring supporting evidence of SLE in the medical record. Results: Using our primary definition of SLE, the incidence during the study period was 4.91/100 000 person-years (95% CI 4.73 to 5.09), with an annual 1.8% decline (p<0.001). In contrast, the prevalence increased from 64.99/100 000 in 1999 (95% CI 62.04 to 67.93) (0.065%) to 97.04/100 000 in 2012 (95% CI 94.18 to 99.90) (0.097%). SLE was six times more common in women. The peak age of incidence was 50–59 years. There was regional variation in both incidence and prevalence. People of Black Caribbean ethnicity had the highest incidence and prevalence. Alternative definitions of SLE increased (definition 2) or decreased (definition 3) estimates of incidence and prevalence, but similar trends were found. Conclusions: The incidence of SLE has been declining but the prevalence has been increasing in the UK in recent years. Age, gender, region and ethnicity are risk factors for SLE. This is the first study to report ethnic differences on the incidence and prevalence of SLE using the CPRD.